Comparative physiological analyses and the genetic basis reveal heat stress responses mechanism among different Betula luminifera populations - Hu, Xian-Ge; Xu, Yilei; Shen, Ning; Liu, Mingtong; Zhuang, Hebi; Borah, Priyanka; Tong, Zaikang; Lin, Erpei; Huang, Huahong (Frontiers in Plant Science, 2022)
Betula luminifera is a subtropical fast-growing timber species with high economic value. However, along with global warming, heat stress become one of the main environmental variables that limit the productivity of B. luminifera, and the response of diverse geographic populations to high temperatures is still unclear. In order to offer a comprehensive understanding of the behavior of B. luminifera under heat stress, the physiological responses of six B. luminifera populations (across the core distribution area) were described in this work in an integrated viewpoint. The results showed that a multi-level physiological regulatory network may exist in B. luminifera, the first response was the activity of resistant enzymes [e.g., peroxidase (POD)] at a preliminary stage of 2 h heat stress, and then the proline (osmoregulation substance) content began to increase after 24 h of continuous high-temperature treatment. In addition, photosynthesis was stronlgly affected by heat stress, and the net photosynthetic rate (Pn) showed a downward trend under heat treatment in all six B. luminifera populations. Interestingly, although the physiological change patterns of the six B. luminifera populations were relatively consistent for the same parameter, there were obvious differences among different populations. Comprehensive analysis revealed that the physiological response of Rongshui (RS) was the most stable, and this was the representative B. luminifera population. Illumina RNA-seq analysis was applied to reveal the specific biological process of B. luminifera under heat stress using the RS population, and a total of 116,484 unigenes were obtained. The differentially expressed genes (DEGs) between different time periods under heat stress were enriched in 34 KEGG pathways, and the limonene and pinene degradation pathway was commonly enriched in all pairwise comparisons. Moreover, transcription factors including bHLH (basic helix–loop–helix), MYB, WRKY, and NAC (NAM, ATAF1/2, and CUC2) were identified. In this study, the physiological response and tolerance mechanisms of B. luminifera under high temperature stress were revealed, which can conducive to the basis of B. luminifera selection and resistance assessment for cultivation and breeding.